1888 Md. Code 468-69 - (:unkn) unknown (My University, 1886)
Concealed Weapons, § 30: Prohibited the carrying of a concealed pistol, dirk knife, Bowie knife, slungshot, billy, sandclub, metal knuckles, razor, or any other dangerous or deadly weapon. Punishable by fine of up to $500 or imprisonment of up to 6 months.
Keywords: CARRY - CONCEALED